Application of Management Theory in Healthcare Service - Waluyo Dwi Cahyono; Yayan Hendayana (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Efecttive healthcare delivery requires the integration of management theories to ensur efficiency, quality, patient safety, and organizational sustainability this paper discuses to application of classical, behavioral, and contemporary managemen theories in healthcare setting. Performance within hospital and primary care system.